Enhanced function of TRPV1 via up‐regulation by insulin‐like growth factor‐1 in a rat model of bone cancer pain. (29th October 2013) - Li, Y.; Cai, J.; Han, Y.; Xiao, X.; Meng, X.L.; Su, L.; Liu, F.Y.; Xing, G.G.; Wan, Y.
Abstract Background Up‐regulation of transient receptor potential vanilloid subfamily, member 1 (TRPV1) is associated with the development and maintenance of cancer pain. The present study aimed to investigate the electrophysiological function of the up‐regulated TRPV1 and the potential regulatory effects of insulin‐like growth factor‐1 (IGF‐1) on TRPV1 expression in peripheral nerves in a rat model of bone cancer pain. Methods A bone cancer pain model of rats was established by injecting MRMT‐1 (rat mammary gland carcinoma cells) breast cancer cells into the tibia bone cavity. Thermal hyperalgesia was assessed by paw‐withdrawal latency to a thermal stimulus, and mechanical allodynia was measured with von Frey monofilaments. TRPV1 and IGF‐1 expression were examined with immunohistochemical staining and Western blot. TRPV1 current density of dorsal root ganglion (DRG) neurons was measured with whole‐cell patch clamping recording technique. Results Rats showed thermal hyperalgesia and mechanical allodynia 14–21 days after MRMT‐1 inoculation into the tibia bone marrow. TRPV1 protein expression and its current density increased in DRG neurons. At the same time, IGF‐1 expression increased in tibia bone cavity, and IGF‐1 incubation increased total or membrane TRPV1 protein expression and TRPV1 current in primary cultured DRG neurons. Inhibition of IGF‐1 receptors in vivo reversed mechanical allodynia and thermal hyperalgesia in rats with bone cancer pain. Conclusion Our results provide novel evidence for the increase of IGF‐1 in tibia bone marrow, which is responsible for the up‐regulation of TRPV1 expression and function in the peripheral nerves of bone cancer pain rats.